Rooted in nature: aesthetics, geometry and structure in the shells of Heinz Isler - Chilton, John; Chuang, Chu-Chun (Springer, 2017)
Reinforced concrete shells frequently constitute the most visible element of a building envelope. They dominate the architectural expression, yet the three-dimensional form is generally determined by the engineer according to its structural efficiency, rather than by the architect according to aesthetical considerations. This raises the question “Who is the author of the design?”